2021
DOI: 10.2337/db20-1210
|View full text |Cite
|
Sign up to set email alerts
|

l-Theanine Activates the Browning of White Adipose Tissue Through the AMPK/α-Ketoglutarate/Prdm16 Axis and Ameliorates Diet-Induced Obesity in Mice

Abstract: l-Theanine is a nonprotein amino acid with much beneficial efficacy. We found that intraperitoneal treatment of the mice with l-theanine (100 mg/kg/day) enhanced adaptive thermogenesis and induced the browning of inguinal white adipose tissue (iWAT) with elevated expression of Prdm16, Ucp1, and other thermogenic genes. Meanwhile, administration of the mice with l-theanine increased energy expenditure. In vitro studies indicated that l-theanine induced the development of brown-like features in adipocytes. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…It has been reported that sirtuin 1 (SIRT1) and PR domain-containing 16 (PRDM16) pathways were also involved in beige fat activation. 47,48 Therefore, further studies are needed to explore whether the anti-obesity effect of WPI is involved in the SIRT1 or PRDM16 pathways. It is well known that FGF21 and irisin are activators of BAT function and WAT browning.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that sirtuin 1 (SIRT1) and PR domain-containing 16 (PRDM16) pathways were also involved in beige fat activation. 47,48 Therefore, further studies are needed to explore whether the anti-obesity effect of WPI is involved in the SIRT1 or PRDM16 pathways. It is well known that FGF21 and irisin are activators of BAT function and WAT browning.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective mechanisms of L-THE include the reduction of oxidative protein and lipid damage as well as the elevation of GSH levels to prevent neurotoxicity and environmental toxin‐induced neuronal cell death in the brain ( Matsuu-Matsuyama et al, 2020 ; Saeed et al, 2020 ). It has been reported that L-THE regulates glucose, lipid, and protein metabolism by promoting the activation of insulin and AMP-activated kinase signaling pathways ( Peng et al, 2021 ). L-THE can decrease the expression of IL-1β, IL-6 and TGF-β though inhibiting the activation of NF‐κB signaling pathway to prevents liver fibrosis ( Pérez-Vargas et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…As AMPK lies on the energy sensing hub, increasing the AMP-ATP ratio would activate AMPK indirectly. There are many natural products that are also AMPK indirect activators, including resveratrol [34], cyptotanshinone [35,36], medicarpin [37], L-theanine [38], crocin [39], sulforaphane [40,41] and platycodin D [42,43] (Table 1). These have all been confirmed to promote brown and beige adipogenesis and/or inhibit white adipogenesis dependent on AMPK activation.…”
Section: Ampk Activatorsmentioning
confidence: 99%
“…C3H10T1/2 is another well-established MSC cell line for adipogenic differentiation studies [44]. L-Theanine, a nonprotein amino acid enriched in green tea, was recently found not only to significantly induce the beiging of subcutaneous WAT in mice, but also ameliorate obesity and improve glucose tolerance and insulin sensitivity in HFD-fed mice [38]. Methyl cinnamate, an active component of Zanthoxylum armatum, inhibited differentiation of 3T3-L1 preadipocytes partially through activation of the CaMKK2-AMPK signaling pathway [45].…”
Section: Ampk Activatorsmentioning
confidence: 99%